1996
DOI: 10.1007/bf02658507
|View full text |Cite
|
Sign up to set email alerts
|

Decreased insulin action and insulin secretion predict the development of impaired glucose tolerance

Abstract: The relative importance of insulin resistance and abnormal insulin secretion as risk factors for the development of impaired glucose tolerance (IGT) is controversial. Few prospective data are available on metabolic precursors of IGT. We examined the relation of fasting serum insulin level (as a marker of insulin resistance) and change in insulin/glucose ratio (delta I30/ delta G30) over the first 30 min after glucose ingestion (as a marker of insulin secretion) as predictors of the 7-year development of IGT in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
65
2
2

Year Published

2000
2000
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(79 citation statements)
references
References 41 publications
10
65
2
2
Order By: Relevance
“…Insulin resistance found in men who further developed isolated IGT is consistent with the increased adiposity found in these men and is concordant with other studies [7,8]. In contrast, men who developed isolated IFG were not characterised by increased insulin resistance at baseline but rather by decreased early insulin secretion.…”
Section: Observationssupporting
confidence: 91%
“…Insulin resistance found in men who further developed isolated IGT is consistent with the increased adiposity found in these men and is concordant with other studies [7,8]. In contrast, men who developed isolated IFG were not characterised by increased insulin resistance at baseline but rather by decreased early insulin secretion.…”
Section: Observationssupporting
confidence: 91%
“…Model C was as model B but was also adjusted for serum phosphate and serum creatinine. All models evaluating the relationship between EIR and serum calcium were also adjusted for M/I, as previous studies have shown that EIR does not seem to provide clinically relevant information except when adjusted for insulin sensitivity [22,23]. Apart from using the whole cohort (n=961) for our analyses, we also used the following prespecified subgroups: 1, normal fasting glucose and glucose tolerance (n=442); 2, normal fasting glucose and glucose tolerance and serum calcium in the normal range (n=413).…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Serum cholesterol and triglycerides were measured by enzymatic methods. Early insulin secretion was calculated using the ratio of the 0-to 30-min incremental insulin values to the 0-to 30-min incremental glucose (4,14).…”
mentioning
confidence: 99%